Topological Abnormalities of Functional Brain Network in Early-Stage Parkinson’s Disease Patients With Mild Cognitive Impairment - Chen, Xiangbin; Liu, Mengting; Wu, Zhibing; Cheng, Hao (Frontiers in Neuroscience, 2020)
Recent studies have demonstrated structural and functional alterations in Parkinson’s disease (PD) with Mild Cognitive Impairment (MCI). However, the topological patterns of functional brain networks in newly diagnosed PD patients with MCI are unclear so far. In this study, we used functional magnetic resonance imaging (fMRI) and graph theory approaches to explore the functional brain network in 45 PD patients with MCI (PD-MCI), 22 PD patients without MCI (PD-nMCI), and 18 healthy controls (HC). We found that PD-MCI, PD-nMCI, and HC groups exhibited small-world architecture in the functional brain network. However, early-stage PD-MCI patient had decreased clustering coefficient, increased characteristic path length, and changed nodal centrality in the default mode network (DMN), control network (CN), somatomotor network (SMN), and visual network (VN), which might contribute to factors for MCI symptoms in PD patients. Our results demonstrated that PD-MCI patients were associated with the disrupted topological organization in the functional network, thus providing a topological network insight into the role of information exchange in the underlying development of MCI symptoms in PD patients.